Asuhan Keperawatan Anak Pada Pasien dengan Kejang Demam di Ruangan Anak RSUD Prof. H. Muhammad Yamin, SH Pariaman Tahun 2026 - Aulia Ramadhani; Prima Yoselina; Reska Handayani; Yessy Aprihatin (CV. ITTC INDONESIA, 2026)
Febrile seizures are seizures that occur due to a rapid and sudden increase in body temperature above 38°C, commonly affecting children aged 3 months to 5 years. Based on data from the World Health Organization (WHO) in 2020, the number of febrile seizure cases exceeded 21.65 million children worldwide. In In donesia, there were 14,251 cases reported in 2023, while in West Sumatra Prov ince there were 1,705 cases. Data from RSUD Prof. H. Muhammad Yamin, S.H Pariaman in 2023–2025 recorded 528 cases of febrile seizures. The purpose of this study was to provide nursing care for children with febrile seizures. The re search method used was a case study approach based on the nursing process, which includes assessment, diagnosis, intervention planning, implementation, and evaluation. The subject of this study was a child (An. A) diagnosed with febrile seizures at RSUD Prof. H. Muhammad Yamin, S.H Pariaman, conducted from February 11 to 15, 2026. The assessment results identified four nursing diagno ses: hyperthermia, ineffective airway clearance, knowledge deficit, and risk of injury. Nursing interventions implemented included monitoring general condition and vital signs, applying warm compresses, monitoring airway patency, and providing education to the family. After five days of nursing care, the patient’s condition improved, as indicated by a decrease in body temperature and increased family understanding. This case study highlights the importance of parental in volvement in supporting the child’s recovery process, especially in recognizing early signs of fever, performing initial management during seizures, and providing appropriate first aid. With adequate knowledge and preparedness, parents can play an active role in maintaining the child’s safety and health.